Impactos da taxa de juros do crédito rural nas demandas por insumos agrícolas - Gurgel, Gustavo Sawaya Amaral (2014)
Rural credit was implemented in Brazil with the intention of accelerating the process of modernization of agriculture and provides capital for funding, investment and commercialization of agricultural production, it has been offered at rates below market rates. The subsidized interest rates are the main attraction of rural credit and strengthen its importance in agriculture as a financing instrument. But problems such as the concentration of resources in producers with higher income, access to credit and capital substitution may compromise the effectiveness of the credit in their purposes. Some studies have reported positive impacts of rural credit in supply and producers income as well as in demand for agricultural inputs. Given the importance of the agricultural sector and considering all the problems associated with credit, is questioned what impact the rural credit demands in agricultural inputs. The work is based on the theory of the firm in competitive markets, assuming that the producer faces restrictions on the purchase of inputs and minimizes the production cost given a production level. From the minimum cost function derive the conditional demands of inputs, which can be influenced by the availability of credit and its interest rate. In the empirical analysis Transcendental Logarithmic (Translog) function was used, that assumes no restrictions on the relationship between the inputs a priori.